Generation of N-waves in laboratory - Lima, Vania Veloso (2019)
In this research work, a novel theoretical first-order formulation for the generation of N-waves in laboratory, by means of a piston-type wave-maker, is presented. The plate's trajectory, velocity and acceleration equations for the generation of tsunami N-waves in a wave flume are deduced. A set of laboratory experiments performed for the generation of leading depression N-waves in a wave basin is described. A Tadepalli-Synolakis N-wave profile is assumed and the equations for the paddle's trajectory, velocity, and acceleration and for the piston stroke and stroke period are derived and discussed in detail. Limits for the initial paddle velocity and acceleration are established. A set of experiments, devised and performed in the 28 m long wave basin of the Laboratory of Hydraulics, at the Faculty of Engineering of the University of Porto, is described. Six leading depression N-waves were selected and classified into three categories, according to their Stokes parameter. The results show that the shorter waves undergo a strong transformation, tending to a solitary wave-like pulse, followed by a trough. The longer waves show a distinct behaviour, tending to a bore-like wave exhibiting a leading trough. The generated longer waves presented the best results when compared with the expected Tadepalli-Synolakis N-wave profiles. Further investigation on the formulation of the wave velocity of the N-waves and on the behaviour of waves with higher order Stokes parameter is necessary.